Uloga visokoškolskih biblioteka u otvorenoj nauci / The Role of Academic Libraries in Open Science - Hajdarpašić, Lejla; Dizdar, Senada (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
Open science includes open access to publications, research data and open educational content, open science redefines the whole process of scientific communication by encouraging dialogue, open review, open sources and tools. Demanding processes of digital transformation of scientific communication require significant support of academic libraries in the processes of advocacy and implementation of open science. Academic libraries in this context, and among other things, need to be recognized as indispensable partners in various open access initiatives at higher education institutions. In this regard, the aim of this research is to establish the specifics and current trends of e-publishing at the University of Sarajevo (UNSA), collect data on active open access journals published by UNSA organizational units, by website content analysis method, and in conclusion to address the benefits of cooperation with libraries of scientific institutions in planning the publishing of scientific journals in open access, as a segment of open science.